Cell-cell interactions drive metastasis of circulating tumor microemboli - Tao, Jianxin; Zhu, Lei; Yakoub, Mina; Reißfelder, Christoph; Loges, Sonja; Schölch, Sebastian (Cancer research, 2022)
Circulating tumor cells are the cellular mediators of distant metastasis in solid malignancies. Their metastatic potential can be augmented by clustering with other tumor cells or nonmalignant cells, forming circulating tumor microemboli (CTM). Cell-cell interactions are key regulators within CTM that convey enhanced metastatic properties, including improved cell survival, immune evasion, and effective extravasation into distant organs. However, the cellular and molecular mechanism of CTM formation, as well as the biology of interactions between tumor cells and immune cells, platelets, and stromal cells in the circulation, remains to be determined. Here, we review the current literature on cell-cell interactions in homotypic and heterotypic CTM and provide perspectives on therapeutic strategies to attenuate CTM-mediated metastasis by targeting cell-cell interactions.